2014
DOI: 10.1007/s00167-014-3491-6
|View full text |Cite
|
Sign up to set email alerts
|

Femoral intercondylar notch width size: a comparison between siblings with and without anterior cruciate ligament injuries

Abstract: Case-control study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Clinically, associations between several morphological traits of the knee and ACL‐injury risk have been widely reported in both sexes across various ages and sports activities. These morphological risk factors, which in vitro studies have found to increase the likelihood of ACL impingement, anterior tibial translation and/or increased ACL peak strains, include ACL cross‐sectional area, femoral intercondylar notch width/shape, and posterior tibial plateau slope . How the morphology of these anatomical traits is biomechanically influenced throughout growth via differentially applied physiological loads is of considerable clinical importance yet remains unclear.…”
mentioning
confidence: 99%
“…Clinically, associations between several morphological traits of the knee and ACL‐injury risk have been widely reported in both sexes across various ages and sports activities. These morphological risk factors, which in vitro studies have found to increase the likelihood of ACL impingement, anterior tibial translation and/or increased ACL peak strains, include ACL cross‐sectional area, femoral intercondylar notch width/shape, and posterior tibial plateau slope . How the morphology of these anatomical traits is biomechanically influenced throughout growth via differentially applied physiological loads is of considerable clinical importance yet remains unclear.…”
mentioning
confidence: 99%
“…5,1822 Patients with left and right bilateral ACL injuries have cut-off value of NWI smaller than unilateral injury patients. 4,8 The reason of ACL injury caused by the intercondylar notch stenosis is variable.…”
Section: Discussionmentioning
confidence: 97%
“…However, both x-ray and CT images have overlapped picture 5 and are influenced by the photograph position heavily, 17 so the error is large. MRI don’t have ghosting, and can display the soft tissue such as joint ligaments clearly, so the error is negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Hewett et al (), multiple risk factors were identified in a pair of female fraternal twins with ACL injuries including increased knee abduction angles, joint and ligament laxity, and decreased femoral intercondylar notch width. Stenotic intercondylar notches were also found to be significantly more frequent in siblings with ACL injuries (Keays, Newcombe, & Keays, ). In addition, other confounding genetic variables could cause increased risk for ACL injury among family members.…”
Section: Discussionmentioning
confidence: 99%